Pengaruh Media Permainan Ular Tangga Numerasi Terhadap Kemampuan Mengenal Lambang Bilangan Pada Anak Usia Dini 4 - 5 Tahun Di TK Palazzo Jaya Bekasi - Azhari, Ayu; Darmiyanti, Astuti; Riana, Nancy (Peneliti.net, 2025)
This research discusses the influence of the numeracy game snakes and ladders on the ability to recognize number symbols in early childhood 4 - 5 years old at the Palazzo Jaya Bekasi Kindergarten. The media for the numeracy snakes and ladders game is included in the learning media in the form of visual media made from large banner material, dice made from flannel and dacron and equipped with other media. The aim of designing this media is to develop the ability to recognize number symbols in children aged 4 - 5 years. The research approach used is a quantitative approach with a pre-experimental research type, one group pretest – posttest design. The population in this study consisted of 15 children. Data collection used in the research was carrying out a pretest as an initial test, then carrying out treatment activities which were carried out in 8 meetings and carrying out posttest activities as a final test. The analysis techniques used are descriptive statistics, normality test using the Kolmogorov-Smirnov test, homogeneity test, and hypothesis testing using paired sample t-test. Based on the results of this research, it can be concluded that the ability to recognize number symbols starts from the age of 4 -5 years. This can be proven by the results of the paired sample t-test, namely the t count obtained a value of 45.121 and the t table of 1.761 so it can be concluded that t count ≥ t table with these rules then Ha is accepted and Ho is rejected and Sig. (2-Tailed) 0.000 < 0.05, then the rule states that Ho is rejected and Ha is accepted, which means that the use of the numeracy snakes and ladders game media has a significant influence on the ability to recognize number symbols in children aged 4 - 5 years at the Palazzo Jaya Bekasi Kindergarten. . Thus, the use of game media can help children develop their ability to recognize number symbols.